The Relationship Between Sedatives, Sedative Strategy, and Healthcare-Associated Infection: A Systematic Review. (20th June 2016) - Caroff, Daniel A.; Szumita, Paul M.; Klompas, Michael
Abstract : BACKGROUND: Healthcare-associated infections (HAIs) cause significant morbidity in critically ill patients. An underappreciated but potentially modifiable risk factor for infection is sedation strategy. Recent trials suggest that choice of sedative agent, depth of sedation, and sedative management can influence HAI risk in mechanically ventilated patients. OBJECTIVE: To better characterize the relationships between sedation strategies and infection. METHODS: Systematic literature review. RESULTS: We found 500 articles and accepted 70 for review. The 3 most common sedatives for mechanically ventilated patients (benzodiazepines, propofol, and dexmedetomidine) have different pharmacologic and immunomodulatory effects that may impact infection risk. Clinical data are limited but retrospective observational series have found associations between sedative use and pneumonia whereas prospective studies of sedative interruptions have reported possible decreases in bloodstream infections, pneumonia, and ventilator-associated events. CONCLUSION: Infection rates appear to be highest with benzodiazepines, intermediate with propofol, and lowest with dexmedetomidine. More data are needed but studies thus far suggest that a better understanding of sedation practices and infection risk may help hospital epidemiologists and critical care practitioners find new ways to mitigate infection risk in critically ill patients. Infect Control Hosp Epidemiol 2016;1–9